Acute pancreatitis as a rare initial manifestation of 99mTc sestamibi negative parathyroid adenoma- a case report - Arunachalam, Kirthika; Thyagarajan, Mohanapriya; Jaghannathan, Kishor Rasipurathanur; Vishwanath, Vineeth (International Journal of Research in Medical Sciences, 2025)
Parathyroid adenoma is the most common cause of hyperparathyroidism. Hypercalcemia secondary to a benign parathyroid adenoma is a rare cause of acute pancreatitis. This report describes a 57-year-old woman who presented to us with acute pancreatitis. On further evaluation, she was found to have elevated calcium and parathyroid hormone levels. Imaging revealed a 99mTc sestamibi-negative parathyroid adenoma. Diagnosis was confirmed by washout parathyroid hormone measurement from the fine needle aspiration cytology (FNAC) sample. The patient then underwent left superior parathyroidectomy. Postoperatively, the patient had no further episodes of acute pancreatitis or other manifestations of hypercalcemia. The mainstay of treatment for patients with primary hyperparathyroidism includes appropriate resuscitation and stabilization with anti-hypercalcaemic measures, such as hydration and forced calciuresis, followed by definitive surgery.